Internet-based cognitive–behavioural therapy for insomnia (ICBT-i): a meta-analysis of randomised controlled trials - Jia Chen; Juan Liu; Yuan-yuan Ye; Ni-ka Chen; Ling Lin; Ya-zhen Liu; Ying Lang; Xun-jun Li; Xin-ju Yang; Xiao-jiang Jiang (BMJ Open)
Objective To evaluate the effectiveness of internet-based cognitive–behavioural therapy for insomnia (ICBT-i) in adults.Design A meta-analysis of ICBT-i.Data sources Systematic searches of randomised controlled trials of ICBT-i were performed in the PubMed, EMBASE, PsycINFO and Cochrane Library databases up to 19 June 2016.Review method 2 reviewers independently performed study selection, quality assessment and data extraction. Outcomes of interest included sleep onset latency (SOL), total sleep time (TST), sleep efficiency (SE), wake after sleep onset (WASO), number of nocturnal awakenings (NWAK), and Insomnia Severity Index (ISI). RevMan 5.2 and Stata 13.0 meta-analysis software were used to perform statistical analysis.Results 14 records for 15 studies (1013 experimental group participants, 591 waiting list group participants) were included. The meta-analysis indicated that, at the post-test time point, SOL decreased by 18.41 min (95% CI 13.60 to 23.21), TST increased by 22.30 min (95% CI 16.38 to 28.23), SE increased by 9.58% (95% CI 7.30% to 11.85%), WASO decreased by 22.31 min (95% CI 13.50 to 31.11), NWAK decreased by 0.52 (95% CI 0.28 to 0.76), and ISI decreased by 5.88 points (95% CI 4.29 to 7.46). Additionally SOL, TST, SE, and WASO exhibited statistically significant improvements at follow-up versus before treatment.Conclusions ICBT-i is an effective treatment for adults with insomnia. This conclusion should be verified in further studies.